The Concept of Private-Administration Contracts in Settling Problems in Government Goods/Services Procurement Contracts - Solechan; Wibawa, Kadek Cahya Susila; Sujoko, Ajik (International Journal of Criminology and Sociology, 2021)
Contracts for the procurement of government goods/services are the realm of private law that implements pure private contracts. A legal relationship in a private contract, especially in a contract settlement, is a relationship between the settlement of the rights and obligations of the parties. This study describes the settlement of government goods/service procurement contracts that require a legal basis both in principle and theory. By using the conceptual analysis method, the findings indicate an inconsistency in solving a legal problem in a government procurement contract, where private legal issues are resolved through administrative law. Theoretically, this study contributes to the resolution of this problem, there are intersections between two legal aspects, namely private law and administrative law. In practical terms, this study encourages the development of government goods/service procurement contract problem-solving practices to adopt the contract problem-solving method starting to use administrative law.